Near-Infrared Time-Resolved Spectroscopy for Assessing Brown Adipose Tissue Density in Humans: A Review - Hamaoka, Takafumi; Nirengi, Shinsuke; Fuse, Sayuri; Amagasa, Shiho; Kime, Ryotaro; Kuroiwa, Miyuki; Endo, Tasuki; Sakane, Naoki; Matsushita, Mami; Saito, Masayuki; Yoneshiro, Takeshi; Kurosawa, Yuko (Frontiers in Endocrinology, 2020)
Brown adipose tissue (BAT) mediates adaptive thermogenesis upon food intake and cold exposure, thus potentially contributing to the prevention of lifestyle-related diseases. 18F–fluorodeoxyglucose (FDG)–positron emission tomography (PET) with computed tomography (CT) (18FDG–PET/CT) is a standard method for assessing BAT activity and volume in humans. 18FDG–PET/CT has several limitations, including high device cost and ionizing radiation and cold exposure necessary to maximally stimulate BAT activity. In contrast, near-infrared spectroscopy (NIRS) has been used for measuring changes in O2-dependent light absorption in the tissue in a non-invasive manner, without using radiation. Among NIRS, time-resolved NIRS (NIRTRS) can quantify the concentrations of oxygenated- and deoxygenated-hemoglobin ([oxy-Hb] and [deoxy-Hb], respectively) by emitting ultra-short (100 ps) light pulses and counts photons, which are scattered and absorbed in the tissue. The basis for assessing BAT density (BAT-d) using NIRTRS is that the vascular density in the supraclavicular region, as estimated using Hb concentration, is higher in BAT than in white adipose tissue. In contrast, relatively low-cost continuous wavelength NIRS (NIRCWS) is employed for measuring relative changes in oxygenation in tissues. In this review, we provide evidence for the validity of NIRTRS and NIRCWS in estimating human BAT characteristics. The indicators (IndNIRS) examined were [oxy-Hb]sup, [deoxy-Hb]sup, total hemoglobin [total-Hb]sup, Hb O2 saturation (StO2sup), and reduced scattering coefficient (s′sup) in the supraclavicular region as determined by NIRTRS, and relative changes in corresponding parameters, as determined by NIRCWS. The evidence comprises the relationships between the IndNIRS investigated, and those determined by 18FDG–PET/CT; the correlation between the IndNIRS and cold-induced thermogenesis; the relationship of the IndNIRS to parameters measured by 18FDG–PET/CT, which responded to seasonal temperature fluctuations; the relationship of the IndNIRS and plasma lipid metabolites; the analogy of the IndNIRS to chronological and anthropometric data; and changes in the IndNIRS following thermogenic food supplementation. The [total-Hb]sup and [oxy-Hb]sup determined by NIRTRS, but not parameters determined by NIRCWS, exhibited significant correlations with cold-induced thermogenesis parameters and plasma androgens in men in winter or analogies to 18FDG–PET. We conclude that NIRTRS can provide useful information for assessing BAT-d in a simple, rapid, non-invasive way, although further validation study is still needed.